EFFECTS OF RHIZOGLOMUS INTRARADICESON PLANT GROWTH AND ROOT ENDOGENOUS HORMONES OF TRIFOLIATE ORANGE UNDER SALT STRESS - Jia-Dong He; Jia-Li Li; Qiang-Sheng Wu (Journal of Animal and Plant Sciences, 2019)
Soil salinity has negative effects on crop growth and production, while it is not clear whether mycorrhizal symbiosis mitigates the negative effect on citrus plants under salt stress. This study was to investigate the effects of an arbuscular mycorrhizal fungus, Rhizoglomus intraradices on plant growth, root morphology, leaf relative water content (RWC), and root endogenous hormone levels of trifoliate orange (Poncirus trifoliata) seedlings exposed to 0 and 150 mmol/L NaCl for 4 weeks. The 150 mmol/L NaCl treatment significantly inhibited root mycorrhizal colonization by 38%. Salt stress significantly reduced plant growth, root morphology, and RWC, while mycorrhizal seedlings represented greater growth performance (height, stem diameter, leaf number, and total plant biomass), root morphological traits (length, area, volume, diameter, and lateral root number) and RWC under non-salt and salt stress. Mycorrhizal fungal inoculation significantly increased root abscisic acid (ABA), indole-3-acetic acid (IAA), and methyl jasmonate (MeJA) levels by 27%, 16%, and 11% under non-salt and by 17%, 20%, and 14% under salt stress. Mycorrhizal treatment did not alter root gibberellins and zeatin riboside levels under non-salt or salt stress, whereas increased root brassinosteroids levels by 24% only under non-salt stress. It suggests that R. intraradices had positive effects on enhancing salt tolerance of trifoliate orange, which is involved in greater plant growth, root development, and root ABA, IAA, and MeJA.
Keywords: arbuscular mycorrhizal fungi; citrus; phytohormone; salt stress